Carotid stenting versus endarterectomy in the same patient: A "direct" comparison. (June 2017) - Ciccone, Marco M; Scicchitano, Pietro; Cortese, Francesca; Gesualdo, Michele; Zito, Annapaola; Carbonara, Rosa; Dentamaro, Ilaria; Pulli, Raffaele; Salerno, Christian; Impedovo, Giovanni; Marinazzo, Davide; Angiletta, Domenico; et al.
The aim of this study was to evaluate outcomes and feasibility of carotid artery stenting versus carotid endarterectomy, both procedures performed in the same patient. Forty-five subjects (33 males, 70 ± 7 years) underwent carotid endarterectomy or carotid artery stenting, the counter procedure on the contralateral carotid performed after a variable period. We evaluated the post-procedural percentage of carotid stenosis at 30, 180 days and one-year follow-up, and the occurrence of acute myocardial infarction, New York Heart Association class progression, stroke, death, cardiovascular death, angina, transient ischemic attack and renal failure. Carotid artery stenting treatment reduced the degree of re-stenosis after 180 days equally to carotid endarterectomy procedure (difference: 0.033%, P  = 0.285). No statistically significant differences were observed according to the occurrence of acute myocardial infarction and New York Heart Association class progression, revealing odds ratio (OR) equal to 0.182 ( P  = 0.361) for acute myocardial infarction and 0.303 ( P  = 0.434) for New York Heart Association class progression. Carotid endarterectomy confirms its efficacy in carotid revascularization, but carotid artery stenting constitutes a good alternative when the procedures are selected based on patient-specific risk factors.